Immunotherapy of mesothelioma: the evolving change of a long-standing therapeutic dream - Calabrò, Luana; Bronte, Giuseppe; Grosso, Federica; Cerbone, Luigi; Delmonte, Angelo; Nicolini, Fabio; Mazza, Massimiliano; Di Giacomo, Anna Maria; Covre, Alessia; Lofiego, Maria Fortunata; Crinò, Lucio; Maio, Michele (Frontiers in Immunology, 2024)
Pleural mesothelioma (PM) is an aggressive and rare disease, characterized by a very poor prognosis.For almost two decades, the world standard treatment regimen for unresectable PM has consisted of a platinum-based drug plus pemetrexed, leading to an overall survival of approximately 12 months.The dramatic therapeutic scenario of PM has recently changed with the entry into the clinic of immune checkpoint inhibition, which has proven to be an effective approach to improve the survival of PM patients. The aim of the present review is to provide a comprehensive overview of the most promising immunotherapeutic-based strategies currently under investigation for advanced PM.